(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In assessing the socio-hygienic conditions of patients diagnosed with oral cavity cancer (OCC), the results of hygienic evaluation of physical condition indicators and the prevalence of existing diseases showed that the average age of patients was 56.2 ± 6.5 years, the average height — 165.2 ± 7.4 cm, and the average body weight — 61.5 ± 4.2 kg. The body mass index (BMI) was 21.8 ± 2.3. According to age distribution, patients were divided into five groups for analysis. The analysis of comorbid diseases revealed that K00–K93 accounted for 51.0%, I00–I99 for 40.4%, and E00–E90 for 12.7%. The evaluation of primary socio-hygienic indicators in patients diagnosed with oral cavity cancer allows for the early identification of risk factors contributing to disease development and associated comorbidities.